LINKS: Scalable, alignment-free scaffolding of draft genomes with long reads. Issue 1 (December 2015) - Warren, René; Yang, Chen; Vandervalk, Benjamin; Behsaz, Bahar; Lagman, Albert; Jones, Steven; Birol, Inanç
Abstract Background Owing to the complexity of the assembly problem, we do not yet have complete genome sequences. The difficulty in assembling reads into finished genomes is exacerbated by sequence repeats and the inability of short reads to capture sufficient genomic information to resolve those problematic regions. In this regard, established and emerging long read technologies show great promise, but their current associated higher error rates typically require computational base correction and/or additional bioinformatics pre-processing before they can be of value. Results We present LINKS, the Long Interval NucleotideK- mer Scaffolder algorithm, a method that makes use of the sequence properties of nanopore sequence data and other error-containing sequence data, to scaffold high-quality genome assemblies, without the need for read alignment or base correction. Here, we show how the contiguity of an ABySSEscherichia coli K-12 genome assembly can be increased greater than five-fold by the use of beta-released Oxford Nanopore Technologies Ltd. long reads and how LINKS leverages long-range information inSaccharomyces cerevisiae W303 nanopore reads to yield assemblies whose resulting contiguity and correctness are on par with or better than that of competing applications. We also present the re-scaffolding of the colossal white spruce (Picea glauca ) draft assembly (PG29, 20 Gbp) and demonstrate how LINKS scales to larger genomes. Conclusions This study highlights the present utility of nanopore reads for genome scaffolding in spite of their current limitations, which are expected to diminish as the nanopore sequencing technology advances. We expect LINKS to have broad utility in harnessing the potential of long reads in connecting high-quality sequences of small and large genome assembly drafts.